Raja Ali Haji (Pengembang Bahasa Melayu Dalam Bentuk Sastra) 1847-2004 - Sania Hidayah; Rusdi Rusdi (Jurusan Sejarah FIS UNP, 2022)
RAJA ALI HAJI BIN HAJI AHMAD (PENGEMBANG BAHASA MELAYU DALAM BENTUK SASTRA) 1847-2004 Sania Hidayah1, Rusdi2 Fakultas Ilmu Sodial, Universitas Negeri Padang Saniahidayah134@gmail.com Abstract This article is a historical study that discussed about Development of Malay language in literary form by Raja Ali Haji. Raja Ali Haji was the central figure of the Malay nation who developed the Malay language in the form of literature which made the Malay language as the forerunner of the Indonesian Language. This research is a qualitative research using historical methods consisting of four stages, namely heuristics, source criticism, interpretation, and historiography. The results of this study concluded that many contemporaries of Raja Ali Haji often made the best works, such as Gurindam Dua Belas, Tuhfat Al-Nahfis and the Book of Malay Language Knowledge which led the Malay language to be an introduction to Indonesian. Raja Ali Haji is a major figure who shines as bright as the works he created to have a positive impact in the field of language and literature until he received the title of National Hero and Mr. Indonesian on November 5, 2004 by President Susilo Bambang Yudhoyono in commemoration of heroes' day. Keywords: Biography, Raja Ali Haji, Language, Malay Literature. Abstrak Artikel ini merupakan kajian sejarah yang membahas mengenai Perkembangan Bahasa Melayu dalam Bentuk Sastra oleh Raja Ali Haji. Raja Ali Haji merupakan tokoh sentral bangsa Melayu yang mengembangkan bahasa Melayu dalam bentuk sastra yang menjadikan bahasa Melayu menjadi cikal-bakal Bahasa Indonesia. Penelitian ini merupakan penelitian kualitatif dengan menggunakan metode sejarah yang terdiri dari empat tahap, yakni heuristik, kritik sumber, interpretasi, dan historiografi. Hasil penelitian ini menyimpulkan bahwa banyak penulis sezaman dengan Raja Ali Haji yang kerap menorehkan karya-karya terbaik, seperti Gurindam Dua Belas, Tuhfat Al-Nahfis serta Kitab Pengetahuan Bahasa Melayu yang mengantarkan Bahasa Melayu menjadi pengantar Bahasa Indonesia. Raja Ali Haji merupakan tokoh utama yang bersinar sebanding dengan karya-karya yang diciptakannya memberikan dampak positif dalam Bidang bahasa dan sastra hingga mendapat gelar Pahlawan Nasional dan Bapak Bahasa Indonesia pada 5 November 2004 oleh Presiden Susilo Bambang Yudhoyono di peringatan hari pahlawan. Kata Kunci: Biografi, Raja Ali Haji, Bahasa, Sastra Melayu.